Online Activism and Political Knowledge among Nigerian Youth during the 2023 Elections: Analyzing the Role of Online Information Sources (Acta Universitatis Danubius. Relationes Internationales, 2024)
This study appraises the nexus between online activism, political knowledge, and the mediating influence of diverse online information sources among Nigerian youth during the 2023 elections. Through an analysis of these relationships, this study contributes to a nuanced understanding of the role digital spaces play in shaping political awareness among young individuals. Specifically, this study seeks to examine whether engagement in online activism during the 2023 Nigerian elections positively correlates with increased levels of political knowledge among Nigerian youth and whether the influence of engagement in online activism on political knowledge is mediated by the extent of exposure to diverse online information sources. This study employs a quantitative approach that incorporates techniques such as Pearson’s correlation and mediation analysis. Data were collected through an online survey of 409 Nigerian youth aged 18–35 years. The findings reveal a significant positive correlation between engagement in online activism and political knowledge, substantiating the hypothesis that active participation in digital advocacy activities enhances political awareness among Nigerian youths. Furthermore, mediation analysis showed that exposure to diverse online information sources mediates the relationship between engagement in online activism and political knowledge, emphasizing the role of online platforms as conduits for political information and awareness. These findings underscore the pivotal role of online platforms in shaping the political knowledge landscape of Nigerian youth during the 2023 elections.